Web-based booking application for services and care products at Lia Salon - Angali, Fransiska Warkop; Yasin, Verdi; Yulianto, Akmal Budi (Jurnal Mandiri IT, 2025)
Digital transformation encourages businesses in various sectors, including the beauty salon industry, to adopt technology as a means of improving efficiency and service. Lia Salon, as one of the beauty service providers, still applies a manual booking system that is considered less efficient and makes it difficult for customers. This research aims to implement a web-based booking application to facilitate the process of booking services and products online. Through a qualitative approach with a prototyping method, the system was developed based on the results of observations and interviews with salon owners and employees. The development results show that the application is able to display service and product information in a structured manner, supports the ordering process directly by customers, and allows automatic management of order data by the admin. With this application, Lia Salon can increase customer convenience as well as operational efficiency. This research recommends the utilization of similar technology for small and medium-sized businesses that face challenges in managing services manually.